(untitled) (Journal of Comparative & International Higher Education, 2023)
The COVID-19 pandemic has caused massive disruption to business as usual across all industries, including education, and there is a growing consensus that the higher education (HE) sector may never go back to ‘business as usual’. While universities are now developing strategies for 2030, several management consultancies are projecting a very challenging HE landscape in the next decade. Suggestions, from the death of the normal university campus to shutdowns, mergers and collaborations are widely predicted including new opportunities for growth. University administrators should develop innovative strategic plans to address the challenges and harness the growth opportunities. Although other industries have faced such disruptions and have coped with responses such as partnerships and mergers, it may be time for universities to reconsider business models for the future. The strategies adopted in the aviation industry have been used to recommend a way forward for universities.